MaxSynBio: Avenues Towards Creating Cells from the Bottom Up. Issue 41 (17th September 2018) - Schwille, Petra; Spatz, Joachim; Landfester, Katharina; Bodenschatz, Eberhard; Herminghaus, Stephan; Sourjik, Victor; Erb, Tobias J.; Bastiaens, Philippe; Lipowsky, Reinhard; Hyman, Anthony; Dabrock, Peter; Baret, Jean‐Christophe; et al.
Abstract: A large German research consortium mainly within the Max Planck Society ("MaxSynBio") was formed to investigate living systems from a fundamental perspective. The research program of MaxSynBio relies solely on the bottom‐up approach to synthetic biology. MaxSynBio focuses on the detailed analysis and understanding of essential processes of life through modular reconstitution in minimal synthetic systems. The ultimate goal is to construct a basic living unit entirely from non‐living components. The fundamental insights gained from the activities in MaxSynBio could eventually be utilized for establishing a new generation of biotechnological processes, which would be based on synthetic cell constructs that replace the natural cells currently used in conventional biotechnology. Abstract : To the Max : A research consortium associated with the Max Planck Society ("MaxSynBio") was formed to investigate living systems from a fundamental perspective. The research program relies solely on the bottom‐up approach and focuses on the detailed analysis and understanding of essential processes of life through modular reconstitution in minimal synthetic systems. The ultimate goal is to construct a basic living unit entirely from non‐living components.